Spin control in reduced-dimensional chiral perovskites - Long, Guankui (2020)
Hybrid organic–inorganic perovskites exhibit strong spin–orbit coupling1, spin-dependent optical selection rules2,3 and large Rashba splitting4–8. These characteristics make them promising candidates for spintronic devices9 with photonic interfaces. Here we report that spin polarization in perovskites can be controlled through chemical design as well as by a magnetic field. We obtain both spin-polarized photon absorption and spin-polarized photoluminescence in reduced-dimensional chiral perovskites through combined strategies of chirality transfer and energy funnelling. A 3% spin-polarized photoluminescence is observed even in the absence of an applied external magnetic field owing to the different emission rates of σ+ and σ− polarized photoluminescence. Three-dimensional perovskites achieve a comparable degree of photoluminescence polarization only under an external magnetic field of 5 T. Our findings pave the way for chiral perovskites as powerful spintronic materials.